Pengaruh Kepemilikan Manajerial, Kebijakan Dividen, Dan Profitabilitas Terhadap Kebijakan Utang Pada Perusahaan Manufaktur Sektor Makanan Dan Minuman Yang Terdaftar Di Bursa Efek Indonesia Periode 2016-2020 - Yentisna Yentisna; Rina Risawati (LPPM Universitas Dharma Andalas, 2022)
This study aims to determine the effect of Managerial Ownership, Dividend Policy, and Profitability on Debt Policy in Food and Beverage Manufacturing Companies Listed on the Indonesia Stock Exchange for the 2016-2020 period, the population in this study amounted to 27 people with a sample of 55 respondents. The data was obtained by looking at the financial statements, then processed and tested using SPSS.From the research conducted, it is known that based on the results of hypothesis testing, it is known that the results of hypothesis testing indicate that. Based on a partial hypothesis test (t test) it shows that the managerial ownership variable has no significant effect on DAR. The DPR variable has a positive and significant effect on DAR. And the ROA variable has no significant effect on DAR.